Investigation of collagen hydrolysate used as carbon and nitrogen source in the fermentation of Bacillus pumilus. (April 2017) - Li, Xia; Zeng, Wei-Cai; Zhu, De-Yi; Feng, Jiang-Ling; Tian, Cui-Cui; Liao, Xue-Pin; Shi, Bi
Graphical abstract: Highlights: The application of collagen hydrolysate (CH) in fermentation process of Bacillus pumilus was first investigated. CH can be used as carbon and nitrogen source in fermentation process, and its utilization degree was enhanced with the introduction of additional carbon source. Growth behaviors of the strain were not affected by the inoculation concentration in the CH contained media. Abstract: This study explored the possible application of collagen hydrolysate (CH) in the fermentation process using Bacillus pumilus as probe bacterial strain. When CH acted as an only source of carbon and nitrogen in the culture medium, B. pumilus was observed to show normal characterizations during its growing process. Meanwhile, the utilization degree of CH by B. pumilus could be enhanced when wheat bran was added (used as carbon source) in the fermentation process. It was found that the highest alkaline protease activity was 325 U/mL when only CH was used, while it was increased to 620 U/mL with the addition of wheat bran. Besides, with different combination of soybean meal and CH, it was found that the ability using CH to produce alkaline protease is comparable to that of soybean meal in the presence of wheat bran. Moreover, the growth behaviors of the strain were not affected by inoculation concentrations, but the time of producing alkaline protease was greatly saved as reducing loading volume. Present investigation suggested that CH can be used as carbon and nitrogen sources in the fermentation process.